Within-drug benefit-risk evaluation of olanzapine long-acting injection at one and two years of treatment - Detke, Holland C.; Lauriello, John; Landry, John; McDonnell, David P. (International Journal of Methods in Psychiatric Research, 2014)
We sought to evaluate the within‐drug benefit‐risk of olanzapine long‐acting injection (LAI) using both quantitative and qualitative methods. Subjects included 1192 adult patients with schizophrenia or schizoaffective disorder who participated in clinical trials with the opportunity for at least two years of continuous treatment with olanzapine LAI (45–405 mg every two to four weeks). Using the Benefit Risk Action Team (BRAT) framework, we evaluated frequency versus duration of benefits and risks commonly observed with atypical antipsychotics. We then used the Transparent Uniform Risk/Benefit Overview (TURBO) method, which weighs the drug's two most medically serious and/or frequent adverse events versus its primary benefit (effectiveness) and an ancillary benefit. The most frequent events among all patients were remaining free of relapse (91.4% for an average of 306 days at one year, 88.4% for 546 days at two years) and symptomatic remission (81.7% for an average of 239 days at one year, 84.1% for 438 days at two years). One‐ and two‐year incidence of ≥7% weight gain was 33.3% and 41.7%. Incidences for sexual dysfunction, hyperprolactinemia, and post‐injection delirium/sedation syndrome (PDSS) were <2%. TURBO ratings unanimously selected PDSS and weight gain as key risks and resulted in an average score in the acceptable benefit‐risk balance range. Copyright © 2014 John Wiley & Sons, Ltd.